Gondolatok a pénzügyi rendszer és a gazdasági növekedés kapcsolatáról - Rácz Tamás Attila (2019)
This study focuses on the relationship between financial development and economic growth. Although numerous empirical studies have been published in the past decades that focus on testing the role of financial development in stimulating economic growth, but most of them are based on theories that appeared in the 1990s. In this paper I try to summarize the theories of the dynamics of these two variables and highlite the most important thoughts from the begining to the present. It will be seen that economists have been dealing with this topic for nearly 150 years, and according to the dominant growth theories and the actual economic policies they had different opinions regarding the importance of the financial system for economic growth. As the world has changed, and the global market became more and more complex, the role of the financial system turned into more and more determining for the economic growth.